2011
DOI: 10.1073/pnas.1106408108
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosa-associated microbiota is influenced by an interaction of Crohn disease and FUT2 ( Secretor ) genotype

Abstract: The FUT2 (Secretor) gene is responsible for the presence of ABO histo-blood group antigens on the gastrointestinal mucosa and in bodily secretions. Individuals lacking a functional copy of FUT2 are known as “nonsecretors” and display an array of differences in susceptibility to infection and disease, including Crohn disease. To determine whether variation in resident microbial communities with respect to FUT2 genotype is a potential factor contributing to susceptibility, we performed 454-based community profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
288
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(312 citation statements)
references
References 66 publications
(71 reference statements)
19
288
4
1
Order By: Relevance
“…The 27F-338R primer pair spanning the hypervariable regions V1 and V2 was used for PCR and barcoded pyrosequencing on the 454 GS-FLX platform with Titanium sequencing chemistry, as previously described (2). Sequences were filtered using MOTHUR v1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 27F-338R primer pair spanning the hypervariable regions V1 and V2 was used for PCR and barcoded pyrosequencing on the 454 GS-FLX platform with Titanium sequencing chemistry, as previously described (2). Sequences were filtered using MOTHUR v1.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies expanded upon these initial observations and identified factors, such as geography, host genetics, diet, and other environmental factors that contribute to interindividual variability in humans (2)(3)(4) and other animals (5-7). However, important questions pertaining to the nature and origins of gut microbial community structure remain to be answered.…”
mentioning
confidence: 99%
“…18,19 In humans, deficiency of FUT2 -which occurs in around 20% of individuals, termed "nonsecretors" -is associated with shifts in microbial composition in the colonic mucosa, feces, and bile. [20][21][22][23] Tsyn deficiency could similarly affect microbial composition by altering nutrient sources and disrupting attachment sites for the intestinal microbiota.…”
mentioning
confidence: 99%
“…how the specific genetic constitution of an individual influences the gut microbial environment is given by the FUT2 association in PSC (and Crohn's disease) [52,53]. Even in healthy individuals, homozygous state for the disease associated variant is associated with substantial alterations in gut microbial community composition [53,54]. The impact of dietary fat on IBD susceptibility represents another example of gene-environment interactions.…”
Section: à8mentioning
confidence: 99%
“…Additional risk loci may be defined by taking a priori knowledge on genetic associations reported in these other phenotypes into account (see [9] for further details). how the specific genetic constitution of an individual influences the gut microbial environment is given by the FUT2 association in PSC (and Crohn's disease) [52,53]. Even in healthy individuals, homozygous state for the disease associated variant is associated with substantial alterations in gut microbial community composition [53,54].…”
Section: à8mentioning
confidence: 99%